COMPARATIVE STUDY OF RICE FARMING INCOME WITH THE APPLICATION OF DIRECT SEED PLANTING SYSTEM (TABELA) AND TRANSPLANTING (TAPIN) - Zahroh, Fatimah Tuz; Romadi, Ugik; Suhirmanto, Suhirmanto (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Over time, the consumption of rice as a food commodity has always increased along with the increase in population. In cultivating rice plants, of course it requires a lot of labor, especially in planting activities. However, the availability of agricultural labor is currently decreasing and the cost is expensive. One technology that can be a solution to this problem is the direct seed planting system (tabela). This study aims to compare farmers' income with the implementation of the two planting systems. Differences in planting systems will affect production costs, so it will also affect farm income. The data analysis used was farm business analysis and independent sample t-test. The results of the analysis found a significant difference between the average income of farmers with tabela and tapin systems. The average income of tabela farmers was Rp 31,373,962/ha/planting season and tapin farmers was Rp 27,267,175 with a difference in income of Rp 4,106,787/ha/planting season.